Trekking ambiental: praticando conceitos e educação ambiental para o ensino médio - Rodrigues, Ramon Juliano [UNESP] (2015)
Trekking Ambiental was a project focusing on high school students from the city of Assis/SP and its objective was to promote a trekking competition among adolescents from four schools, making the event an environmental education tool to talk about Environmental issues fun and easier. Furthermore, the project aimed to expand the city’s sports culture and bring the practice of theories that are learned at school, improving the people’s ability to read and interpret maps and spreadsheets, and share environmental awareness and a sense of orientation space-time. For this, during 2014 trainings were organized with participants aiming at the final event, which was attended by about 100 people, including students, competitors, teachers and the organization’s team.